Unaccompanied Minor Asylum-Seekers in Switzerland - A Critical Appraisal of Procedures, Conditions and Recent Changes - Samuel Keller; Eva Mey; Thomas Gabriel (Social Work & Society, 2017)
The article gives a critical view on the situation of unaccompanied minor asylum-seekers in Switzerland. Available data on the situation of "unaccompanied minors" (UAM) in Switzerland are presented and discussed. Further the Swiss Legal framework and policy as well as the impact of the The United Nations Convention on the Rights of the Child is critically reviewed due to their situation. The article shows current proceedings but it shows also that UAMs' rights and needs in Switzerland are not (yet) met by the process steps between the border and appropriate accommodation, or by the understanding and coordination between asylum policy and child and youth care.